2022
DOI: 10.1128/spectrum.00170-22
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiota Metabolism in Obesity-Related Type 2 Diabetes Reduces Osteomyelitis Severity

Abstract: Individuals with obesity-related type 2 diabetes (obesity/T2D) are at a five times increased risk for invasive Staphylococcus aureus osteomyelitis (bone infection) following orthopedic surgeries. With increasing antibiotic resistance and limited discoveries of novel antibiotics, it is imperative that we explore other avenues for therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 91 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…Enteral feeding also increases the risks of reflux and changes in the pH or urea content ( 43 ). Several reports ( 33 , 34 ) have shown that the intestinal microbiota composition was one of the factors responsible for the enhancement of intestinal permeability. To our knowledge, this is the first report to clarify that enteral feeding has additional effects on translocation from rectal carriage to clinical infection associated with CRE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enteral feeding also increases the risks of reflux and changes in the pH or urea content ( 43 ). Several reports ( 33 , 34 ) have shown that the intestinal microbiota composition was one of the factors responsible for the enhancement of intestinal permeability. To our knowledge, this is the first report to clarify that enteral feeding has additional effects on translocation from rectal carriage to clinical infection associated with CRE.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of the intestine by nonhost niche microorganisms can lead to a permeable gut through various mechanisms ( 30 38 ), by either being directly responsible for the features of inflammation ( 30 32 ) or favoring microbe-microbe and microbe-host interactions such as regulating the diversity and community composition of the cecal microbiome ( 33 , 34 ), manipulating bacterial metabolites ( 35 , 36 ), participating the innate and the adaptive immune responses ( 37 ), and penetrating host barriers ( 38 ), allowing colonizing microorganisms to invade the intestinal tissue and leading to subsequent translocated infection.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing antibiotic resistance and limited discoveries of novel antibiotics, it is imperative that need to explore other avenues for therapeutics [67]. Han et al reported that regulating the relationship between phages and bacteria can maintain the health of the body and even reverse diseases [68].…”
Section: Medicine Advancesmentioning
confidence: 99%
“…Additionally, the gut microbiota is closely associated with serum metabolites, and it may bridge the distance between the gut and distant organs 27 . Modulating the gut microbiota can alter serum metabolites, a mechanism that can alter the treatment of several diseases 28–30 . Likewise, it may be possible to alleviate periodontal bone destruction in patients with DMP by ingestion of probiotics, with regulation of the gut microbiota dysbiosis and alterations in serum metabolites as potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%